Embodied Cognition, Perception, and Performance in Music - Geeves, Andrew; Sutton, John (Empirical Musicology Review, 2015)
In this response to Leman and Maes’s paper in this issue, we raise a couple of concerns about the authors’ particular approach to embodied music cognition, drawing selectively on their other writings to enrich our interpretation of this target article, while pointing to a few of the many other legitimate research paths that can also fall under this label. We explore two underlying dichotomies implicit in the research programme adumbrated by Leman and Maes – cognition/embodiment and perception/performance – and implications for their theory of embodied music cognition. We then examine research that has focussed on the perspective of the music performer.